High-speed nanoscale tribology enabled by combined QCM/AFM - Celik, Umit; Celik, Kuebra; Kehribar, Ihsan; Celik, Suleyman; Baykara, Mehmet Z. (Elsevier, 2023)
Forming a fundamental understanding of tribological processes on the atomic scale has the potential to revolutionize the control of friction and wear in macroscopic mechanical systems. On the other hand, methods such as atomic force microscopy (AFM) that provide nanoscale spatial resolution are severely limited in terms of scanning speed when compared with macroscopic mechanical processes, leading to a speed gap between fundamental and applied tribology that spans several orders of magnitude. Here, we propose a new method combining AFM experiments with simultaneous quartz crystal microbalance (QCM) measurements for highspeed nanoscale tribology. In particular, scanning speed and vibration amplitude are controlled by QCM whereas normal loads are controlled by AFM. Complementary data are simultaneously recorded in the form of nanoscale, two-dimensional maps of frequency shifts and lateral forces provided by the QCM and AFM, respectively. Proof-of-principle results are presented on a gold-coated QCM sensor surface patterned with a graphene array, whereby stick and partial slip regimes are observed as a function of sliding speed.
Keywords: Atomic Force Microscopy (AFM); Friction; Nanotribology; Quartz Crystal Microbalance (QCM)